Strategi Pengembangan Usaha Budidaya Ikan Konsumsi Air Tawar dan Ikan Hias Air Tawar pada Kelompok Mitra Posikandu Kabupaten Bogor - Nugroho, Bagus Dwi; Hardjomidjojo, Hartrisari; Sarma, Ma'mun (Institut Pertanian Bogor, 2017)
Fisheries is a prominent sector in Bogor District, in line with its vision to be the most advanced district in Indonesia by becoming the biggest producer of both decorative and consumable fish. Total production of consumable fish has reached 112.781 tons and production of decorative fish has reached 242.520.230 seeds. Kelompok Mitra Posikandu is a group of fish breeder which is located in Minapolitan Area, Bogor District. The group was established in August 2016 with 23 members. The newly established group has several potencies to grow and expand, hence need a research to be carrried out. Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) methods were used in this research to analyze both internal and external factors. Alternative strategies for business expansion were explained with Strengths, Weaknesses, Opportunities and Threats (SWOT) method and further analyzed by using Analytical Hierarchy Process (AHP).